2014
DOI: 10.1177/1535370214561958
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin prevents angiotensin II-induced cardiac hypertrophy and myocardial superoxide generation

Abstract: Our studies and others recently demonstrate that polydatin, a resveratrol glucoside, has antioxidative and cardioprotective effects. This study aims to investigate the direct effects of polydatin on Ang II-induced cardiac hypertrophy to explore the potential role of polydatin in cardioprotection. Our results showed that in primary cultured cardiomyocytes, polydatin blocked Ang II-induced cardiac hypertrophy in a dose-dependent manner, which were associated with reduction in the cell surface area and [(3)H]leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The further studies show that polydatin protects against cardiac ischemia–reperfusion injury by modulating renin-angiotensin system and reducing ROS production [ 22 24 ], attenuates the cardiac dysfunction generated by burn through inhibiting ryanodine receptors [ 25 ], and alleviates cardiac dysfunction and mitochondrial function in the diabetic model [ 26 ]. In line with above findings, our study shows that polydatin protects against angiotensin II-induced cardiac hypertrophy both in vitro and in vivo through suppression of NADPH oxidase activity and superoxide production [ 27 ]. In addition, our previous studies have also shown that polydatin inhibits insulin resistance and improves hepatic steatosis [ 28 ].…”
Section: Introductionsupporting
confidence: 83%
“…The further studies show that polydatin protects against cardiac ischemia–reperfusion injury by modulating renin-angiotensin system and reducing ROS production [ 22 24 ], attenuates the cardiac dysfunction generated by burn through inhibiting ryanodine receptors [ 25 ], and alleviates cardiac dysfunction and mitochondrial function in the diabetic model [ 26 ]. In line with above findings, our study shows that polydatin protects against angiotensin II-induced cardiac hypertrophy both in vitro and in vivo through suppression of NADPH oxidase activity and superoxide production [ 27 ]. In addition, our previous studies have also shown that polydatin inhibits insulin resistance and improves hepatic steatosis [ 28 ].…”
Section: Introductionsupporting
confidence: 83%
“…PD possesses antioxidative and anti‐inflammatory activities (Mohan et al, ). Previous studies have demonstrated the therapeutic effects of PD in HG‐induced injury in multiple organs, including heart, liver, and brain (Xu et al, ; Zhang, Tan, Zhang, & Yao, ). To test the safety of PD, we administered a single large PD dose of 5000 mg/kg body weight to mice and observed no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…PD has been shown to possess antioxidant and anti‐inflammatory activities (Mohan et al, ). Previous studies have demonstrated the therapeutic effects of PD on HG‐induced injury in multiple organs, including the heart, liver, and brain (Xu et al, ; Zhang et al, ). In the present study, we observed that PD decreased all of the analyzed markers of renal dysfunction (Table ) in KKAy mice, suggesting that PD possesses renoprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the existing literature referencing resveratrol and Ang II in whole animal studies is surprisingly sparse. Polydatin, a resveratrol glucoside, was delivered in an Ang II-induced model of hypertension by Zhang et al, 26 who found that the chronic infusion of Ang II significantly increased systolic blood pressure from 120±3 to 162±7 mmHg with Ang II, and oral administration of polydatin for 5 weeks did not decrease the pressor effect of Ang II. Dolinsky et al 3 implanted mice with osmotic minipumps to deliver Ang II (1.4 mg/kg/d) and placed mice on a diet containing resveratrol (using ~320 mg/kg/d resveratrol).…”
Section: Discussionmentioning
confidence: 99%